2015
DOI: 10.1257/mic.20130164
|View full text |Cite
|
Sign up to set email alerts
|

Quality Disclosure Programs and Internal Organizational Practices: Evidence from Airline Flight Delays

Abstract: Disclosure programs exist in many industries in which consumersQ uality disclosure programs exist in many industries in which consumers are imperfectly informed about product quality.1 A growing empirical literature on disclosure programs has documented that disclosure can facilitate better matches between consumers and suppliers and improve the level of quality supplied by firms. However, there is also evidence that disclosure programs can have unanticipated and, in some cases, undesirable outcomes if firms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…In the article by Zámková, Prokop (2015a) it was proved that the delays caused by the air traffic control at Czech airports are more frequent at night and during the evening, whereas it has now been found that at European airports this reason is more prevalent in the morning. According to Forbes, Lederman, Tombe (2015) airlines should release information about the number of flights delayed by longer than 15 minutes. In our opinion it would be very useful if all airlines reported these data publicly.…”
Section: Resultsmentioning
confidence: 99%
“…In the article by Zámková, Prokop (2015a) it was proved that the delays caused by the air traffic control at Czech airports are more frequent at night and during the evening, whereas it has now been found that at European airports this reason is more prevalent in the morning. According to Forbes, Lederman, Tombe (2015) airlines should release information about the number of flights delayed by longer than 15 minutes. In our opinion it would be very useful if all airlines reported these data publicly.…”
Section: Resultsmentioning
confidence: 99%
“…Forbes et al (2012) find that airline personnel who are rewarded for on-time performance reduce taxi-in times only when the expected arrival time is just around the critical threshold for the flight being recorded as 'late'. Schweitzer et al (2004) and Cadsby et al (2010) find in lab experiments that non-linear incentive schemes invite substantial lying to meet the target.…”
Section: Introductionmentioning
confidence: 85%
“…Possibly, we do not have a sufficiently large number of observations to identify region-specific week fixed effects as well as the effect of intermediate relative performance split out by week. 24 Next, to assess the exogeneity of our instrument we conducted a placebo-experiment. In particular, we pretend that our experiment would have taken place in weeks 1-4 instead of weeks 5-8 of 2010, following similar estimation procedures as above.…”
Section: Robustness Checksmentioning
confidence: 99%
“…In the cases documented by Jacob and Levitt (2003), Figlio and Getzler (2006), and Forbes et al (2015), producers were able to practice manipulation independently. When disclosed information is collected by inspection, manipulation likely requires the inspector's involvement.…”
mentioning
confidence: 99%
“…While this need for complicity creates an initial hurdle to manipulation, corruption could be quite pervasive if that hurdle is cleared. After all, it is the inspectors who 4 Notably, Forbes et al (2015) assess mandatory disclosure by US airlines of the fraction of their flights which are more than 15 minutes late. They find that some airlines respond strongly, shifting attention toward flights expected to be around 15 minutes late, and some do not respond at all.…”
mentioning
confidence: 99%